CFD simulation of solid-liquid stirred tanks for low to dense solid loading systems - Wadnerkar, Divyamaan; Tade, Moses; Pareek, Vishnu; Utikar, Ranjeet (2015)
The hydrodynamics of suspension of solids in liquids are critical to the design and performance of stirred tanks as mixing systems. Modelling a multiphase stirred tank at a high solids concentration is complex owing to particle-particle and particle-wall interactions which are generally neglected at low concentrations. Most models do not consider such interactions and deviate significantly from experimental data. Furthermore, drag force, turbulence and turbulent dispersion play a crucial role and need to be precisely known in predicting local hydrodynamics. Therefore, critical factors such as the modelling approach, drag, dispersion, coefficient of restitution and turbulence are examined and discussed exhaustively in this paper. The Euler-Euler approach with kinetic theory of granular flow, Syamlal-O'Brien drag model and Reynolds stress turbulence model provide realistic predictions for such systems. The contribution of the turbulent dispersion force in improving the prediction is marginal but cannot be neglected at low solids volume fractions. Inferences drawn from the study and the finalised models will be instrumental in accurately simulating the solids suspension in stirred tanks for a wide range of conditions. These models can be used in simulations to obtain precise results needed for an in-depth understanding of hydrodynamics in stirred tanks.